Synthesis techniques for polymer nanocomposites - Mittal, Vikas (Polymer nano-, micro- & macrocomposites., 2015)
Summarizing all the most important synthesis techniques used in the lab as well as in industry, this book is comprehensive in its coverage from chemical, physical and mechanical viewpoints. In a self-contained manner, the text guides readers in choosing the correct synthesis routes, such as suspension and miniemulsion polymerization, living polymerization, sonication, mechanical methods or the use of radiation, and so achieve the desired composite properties.